2005
DOI: 10.1016/j.jvb.2003.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Socialization and development of the work ethic among adolescents and young adults

Abstract: Work ethic is part of a broader field of attitudes, identified as cultural conservatism. The results of this longitudinal study-three repeated measurements with 620 adolescents and one of their parents as participants-show that parentsÕ social economic status and educational level are associated with their cultural conservatism, and with the educational level and cultural conservatism of their children. During adolescence, parents effectively transfer their own cultural (non-)conservatism to their children. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 21 publications
2
34
1
Order By: Relevance
“…While research highlights the need for improvements in educational systems and institutions of the Arab world, it offers no evidence for a link between poor education and poor work ethic as suggested by Sidani and Thornberry (2009). Rather, evidence from the wider literature supports the directly opposite view, that individuals with poor educational backgrounds can have higher work ethics (Darnell and Sherkat 1997;Dunn 2010;ter Bogt et al 2005). Lastly, Sidani and Thornberry (2009) propose management styles in the Arab context as contributing to what they view as a dysfunctional Arab work ethic.…”
Section: Motivation For the Current Studymentioning
confidence: 98%
See 1 more Smart Citation
“…While research highlights the need for improvements in educational systems and institutions of the Arab world, it offers no evidence for a link between poor education and poor work ethic as suggested by Sidani and Thornberry (2009). Rather, evidence from the wider literature supports the directly opposite view, that individuals with poor educational backgrounds can have higher work ethics (Darnell and Sherkat 1997;Dunn 2010;ter Bogt et al 2005). Lastly, Sidani and Thornberry (2009) propose management styles in the Arab context as contributing to what they view as a dysfunctional Arab work ethic.…”
Section: Motivation For the Current Studymentioning
confidence: 98%
“…Their intention to take entry-level positions and eventually become the driving force of the corporate world positions them at an interesting cross-roads between the values imbued in them through their social development and the values they will be immersed in when they engage with the workplace (Rest and Narvaez 1994). Work values that are formed by adolescence have been found to be predictive of values held later in life (ter Bogt et al 2005). The work ethic concept represents a perception of the value of work, The importance of the sample current sample should not be underestimated as ''one's perceptions … have stronger potential impact on principles and practices in work life'' (Aygün et al 2008, p. 211).…”
Section: Data Collectionmentioning
confidence: 99%
“…Specifically, work ethic pertains to workrelated activity, refers to a general approach toward accomplishment and may generalise to other domains, such as education. Work ethic operates as a personality construct (Merrens & Garrett, 1975;Mirels & Garrett, 1971) and remains stable over time (ter Bogt, Raaijmakers, & van Wel, 2005). According to Miller et al and measured by their multidimensional work ethic profile (MWEP), work ethic is composed of seven sub-components: (a) centrality of work, a belief that work is important in its own right, (b) self-reliance, representing a drive toward independence in task accomplishment, (c) hard work, the belief that an increased level of effort is the key to effective task accomplishment, (d) leisure, a value on downtime/non-work activities, (e) morality/ethics, a proclivity to engage in just/moral behaviour, (f ) delay of gratification, the capacity to postpone rewards until a later date, and (g) wasted time, a value regarding the productive use of time.…”
mentioning
confidence: 99%
“…People with a lower education level had a stronger work ethic than people with a higher education level. An explanation for these differences might be that working class parents with less education prepare their children to accept certain standards and norms and be aware of the inflexible working environment they are likely to encounter, while middle class parents with a higher education level prepare their children they have to be able to regulate work independently at the occupational level they will probably face (Ebadollahi Chanzanagh & Akbarnejad, 2011;Ter Bogt et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is defined as "a set of beliefs and attitudes, reflecting the fundamental value of work" (Meriac, Woehr, & Banister, 2010, p. 316). Previous authors have suggested that it is a relatively stable type of attitude (Ter Bogt, Raaijmakers, & Van Wel, 2005). Work ethics not only concerns work but also the relationship with others at work.…”
Section: Work Ethicmentioning
confidence: 99%